Women's pelvic floor muscle strength and urinary and anal incontinence after childbirth: a cross-sectional study - Priscila Tavares Zizzi; Karina Fernandes Trevisan; Nathalie Leister; Camila da Silva Cruz; Maria Luiza Gonzalez Riesco
Abstract OBJECTIVE To analyse pelvic floor muscle strength (PFMS) and urinary and anal incontinence (UI and AI) in the postpartum period. METHOD Cross-sectional study carried out with women in their first seven months after child birth. Data were collected through interviews, perineometry (Peritron™), and the International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF). RESULTS 128 women participated in the study. The PFMS mean was 33.1 (SD=16.0) cmH2O and the prevalence of UI and AI was 7.8% and 5.5%, respectively. In the multiple analyses, the variables associated with PFMS were type of birth and cohabitation with a partner. Newborn's weight, previous pregnancy, UI during pregnancy, and sexual activity showed an association with UI after child birth. Only AI prior to pregnancy was associated with AI after childbirth. CONCLUSION Vaginal birth predisposes to the reduction of PFMS, and caesarean section had a protective effect to its reduction. The occurrence of UI during pregnancy is a predictor of UI after childbirth, and women with previous pregnancies and newborns with higher weights are more likely to have UI after childbirth.AI prior to pregnancy is the only risk factor for its occurrence after childbirth. Associations between PFMS and cohabitation with a partner, and between UI and sexual activity do not make possible to conclude that these variables are directly associated.